2021
DOI: 10.1111/1759-7714.14246
|View full text |Cite
|
Sign up to set email alerts
|

Utility of mass spectrometry and artificial intelligence for differentiating primary lung adenocarcinoma and colorectal metastatic pulmonary tumor

Abstract: Background: Rapid intraoperative diagnosis for unconfirmed pulmonary tumor is extremely important for determining the optimal surgical procedure (lobectomy or sublobar resection). Attempts to diagnose malignant tumors using mass spectrometry (MS) have recently been described. This study evaluated the usefulness of MS and artificial intelligence (AI) for differentiating primary lung adenocarcinoma (PLAC) and colorectal metastatic pulmonary tumor. Methods: Pulmonary samples from 40 patients who underwent pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 56 Through the analysis of almost 300 cancerous and healthy tissue samples, the authors demonstrated the technique to have a high sensitivity and specificity, with a diagnostic accuracy of 92%. PESI‐MS was also recently applied to the analysis of pulmonary tumors 57 and liver tumours across different populations, highlighting its versatility with different tissue types. 58 Although PESI has been widely applied to the analysis of cancerous tissues, it does still require tissue biopsy, as opposed to techniques such as REIMS which can be used in situ in the operating theatre and could feasibly be used for non‐invasive analysis.…”
Section: Applications Of Aimsmentioning
confidence: 99%
“… 56 Through the analysis of almost 300 cancerous and healthy tissue samples, the authors demonstrated the technique to have a high sensitivity and specificity, with a diagnostic accuracy of 92%. PESI‐MS was also recently applied to the analysis of pulmonary tumors 57 and liver tumours across different populations, highlighting its versatility with different tissue types. 58 Although PESI has been widely applied to the analysis of cancerous tissues, it does still require tissue biopsy, as opposed to techniques such as REIMS which can be used in situ in the operating theatre and could feasibly be used for non‐invasive analysis.…”
Section: Applications Of Aimsmentioning
confidence: 99%
“…Liquid chromatography–tandem mass spectrometry (LC–MS/MS) have been developed as an innovative tool for the analysis of small samples, offering improved specificity over traditional methods. MS imaging and probe electrospray ionization (PESI)‐mass spectrometry have been described as useful tools for diagnosing lung cancer or distinguishing between normal and cancerous tissues 11,12 . PESI‐MS allows rapid evaluation and is extremely useful, but has the weakness of being able to measure only that part of the specimen obtained by puncture biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…MS imaging and probe electrospray ionization (PESI)‐mass spectrometry have been described as useful tools for diagnosing lung cancer or distinguishing between normal and cancerous tissues. 11 , 12 PESI‐MS allows rapid evaluation and is extremely useful, but has the weakness of being able to measure only that part of the specimen obtained by puncture biopsy. However, diagnostic procedures to detect specific substances by LC–MS/MS in the field of lung cancer have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In medical image proce ssing, DL techniques have advantages such as high accuracy and strong adapta bility. In recent years, with the rapid development of DL technology, an increa sing number of scholars have harnessed it for medical domain, and great stride s have been made [21][22][23] . However,there are relatively few studies on the constr uction of lung adenocarcinoma data set and intelligent detection,which conflict s with the urgent treatment needs.…”
Section: Introductionmentioning
confidence: 99%